A new species of the genus Hyalessa (Hemiptera, Cicadidae) from China, with DNA barcoding data and a key to related species - Wang, Xu; Qiu, Yue; Wei, Cong (Zootaxa, 2016)
One new species of the genus Hyalessa China, H. wangi sp. nov., from Yunnan, China is described. Partial mitochondrial COI gene (DNA barcoding) of this new species is sequenced and uploaded to GenBank. A key to all species of Hyalessa is provided.